Calcio-herbal medicine Divya-Swasari-Vati demonstrates acceptable non-clinical safety profile in the repeated-dose 28-day subacute oral toxicity study in Sprague-Dawley rats, under GLP compliance - Balkrishna, Acharya; Sinha, Sandeep; Varshney, Anurag (Frontiers in Pharmacology, 2025)
IntroductionAyurvedic medicines with scientifically proven anti-inflammatory, bronchodilator, anti-tussive and anti-microbial activities have an immense potential to be repurposed for the management of obstructive airway symptoms, frequently encountered in patients afflicted with coronavirus disease 2019 (COVID-19). Divya-Swasari-Vati is an Ayurvedic prescription medicine, which contains nine botanical drugs and seven mineral ashes. The individual botanical drugs and minerals present in Divya-Swasari-Vati have been traditionally used for the treatment of upper and lower respiratory tract symptoms, associated with ailments ranging from common cold and cough to chronic asthma and respiratory infections. Divya-Swasari-Vati is enriched with metabolites known to possess pharmacological activity and has demonstrated in-vivo anti-inflammatory effects in a human A549 cell line-xenotransplanted zebrafish model, subsequent to challenge with the spike protein of severe acute respiratory syndrome-coronavirus-2. With an objective to support the preclinical and clinical profile, the non-clinical safety assessment of Divya-Swasari-Vati is highly warranted. Accordingly, in the current study, we report the non-clinical safety of Divya-Swasari-Vati in a repeated-dose, 28-day subacute oral toxicity study, followed by a 14-day recovery period, in Sprague-Dawley rats, under GLP compliance.MethodsThis toxicological study was conducted according to Organization for Economic Cooperation and Development (OECD) test guideline 407 and in conformance with the OECD principles of Good Laboratory Practice (GLP). Divya-Swasari-Vati was tested at the doses of 100, 300 and 1,000 mg/kg/day, in five males and five female rats of each experimental group.ResultsIn the present study, no mortality or morbidity was observed in any of the test groups. Furthermore, Divya-Swasari-Vati treatment was not associated with any toxicologically relevant outcomes with respect to clinical signs as well as clinical-, gross- and histo-pathological findings, as compared to the vehicle-administered group. Consequently, the No-Observed-Adverse-Effect-Level (NOAEL) of Divya-Swasari-Vati was determined to be 1,000 mg/kg/day, in both male and female rats.DiscussionThe acceptable safety profile of Divya-Swasari-Vati demonstrated in the present study, provisions for its future non-clinical safety assessments for longer duration in rodents as well as in higher animals. Additionally, this study also serves as the first step towards the detailed assessment of Divya-Swasari-Vati in clinical settings.